Pashto language stemming algorithm - Aslamzai, Sebghatullah; Saidah Saad (Penerbit Universiti Kebangsaan Malaysia, 2015)
This paper presents a stemming algorithm for morphological analysis for less popular or minor language like Pashto language. There is lack of resources and tools that can be applied in different applications such as in document indexing, clustering, language processing, text analysis, database search systems, information retrieval, and linguistic applications. The review of literature shows that only a few morphological studies have been conducted in the Pashto language, and research which focused on automatic stemming has not yet been fully analysed. In addition, no stemming algorithm has been proposed for extracting Pashto root words from the Pashto corpus, which is applicable for the above mentioned functions. Therefore, the objective of the current thesis is to develop a rule-based stemming algorithm for the Pashto language. The Pashto corpus is directly used as the input and the stemming algorithm uses both inflectional and derivational morphemes. The output is in the form of meaningful root word without affixes. Furthermore, the accuracy and strength of the proposed algorithm is evaluated using word count method. To validate the function of the developed algorithm, two native speakers of Pashto were recruited to evaluate the algorithm in terms of its accuracy and strength. The result of the study shows that the proposed algorithm has the accuracy of 87%. This study can have a great contribution to Pashto language in terms of extracting the root words useful for different purposes including data indexing, information retrieval, linguistic application, etc. This research also lays the ground for further studies on Pashto language analysis.